American Intelligence : Small-Town News and Political Culture in Federalist New Hampshire - Lafferty, Ben (Book collections on Project MUSE., 2019)
"The rapid expansion of the newspaper business in the first decade of the American republic had crucial consequences for cultural, commercial, and political life in the early United States, as the nation went from having dozens of weekly newspapers to hundreds. Before organized newsrooms and bureaus came on the scene, these fledgling publications were filled with content copied from other newspapers as well as letters, poems, religious tracts, and ribald anecdotes submitted by readers. Taking up the New Hampshire newspaper industry as its case study, American Intelligence unpacks the ways in which an unprecedented quantity of printed material was gathered, distributed, marketed, and consumed, as well as the strong influence that it had on the shaping of the American political imagination. Ben P. Lafferty also considers the lives of the printers themselves and asks why so many men chose to pursue such a fraught and turbulent profession. This snapshot resonates with the contemporary media-saturated and politically chaotic age"--